Napster and New Zealand: Authorisation Under the Copyright Act 1994 - Apáthy, Paul (Victoria University of Wellington Law Review, 2002)
This article critically examines the concept of authorisation under the Copyright Act 1994 and considers how New Zealand courts might deal with the issues raised by the Napster litigation in the United States.